The Influence of Capital, Labor, Length of Business, and Information Technology on the Income of Coffee Shop MSMEs in Denpasar City - Putri, Novita Ramadhani Heriani; Saskara, Ida Ayu Gde Dyastari (Business and Investment Review, 2025)
The culinary sector in Denpasar City shows rapid development along with increasing public consumption and modern lifestyle trends, one of which is marked by the proliferation of coffee shop. The significant growth in the number of coffee shop in Denpasar City has triggered increasingly fierce competition among business actors in obtaining income. This study aims to determine the effect of capital, labor, length of business, and the use of information technology on the income of coffee shop MSMEs in Denpasar City. This research method uses a quantitative method with a population of 176 coffee shop MSMEs in Denpasar City with a sample of 64 business units. The method for determining the research sample was determined proportionally through proportionate stratified random sampling technique and respondents were collected using purposive sampling method in four sub-districts in Denpasar City. The data analysis technique used multiple linear regression analysis. The results of this study indicate that capital, labor, length of business, and information technology have a simultaneous and significant effect on the income of coffee shop MSMEs in Denpasar City. In addition, capital, labor, length of business, and information technology partially have a positive effect on the income of coffee shop MSMEs in Denpasar City. The implication of this research is that increasing capital, number of workers, business experience and utilization of information technology can increase the income obtained by coffee shop MSMEs in Denpasar City.